An Insight into the Phase Transformation of WS2 upon Fluorination. Issue 44 (21st September 2018) - Radhakrishnan, Sruthi; Das, Deya; Deng, Liangzi; Sudeep, Parambath M.; Colas, Guillaume; de los Reyes, Carlos A.; Yazdi, Sadegh; Chu, Ching Wu; Martí, Angel A.; Tiwary, Chandra Sekhar; Filleter, Tobin; Singh, Abhishek K.; et al.
Abstract: The transformation from semiconducting to metallic phase, accompanied by a structural transition in 2D transition metal dichalcogenides has attracted the attention of the researchers worldwide. The unconventional structural transformation of fluorinated WS2 (FWS2 ) into the 1T phase is described. The energy difference between the two phases debugs this transition, as fluorination enhances the stability of 1T FWS2 and makes it energetically favorable at higher F concentration. Investigation of the electronic and optical nature of FWS2 is supplemented by possible band structures and bandgap calculations. Magnetic centers in the 1T phase appear in FWS2 possibly due to the introduction of defect sites. A direct consequence of the phase transition and associated increase in interlayer spacing is a change in friction behavior. Friction force microscopy is used to determine this effect of functionalization accompanied phase transformation. Abstract : The transformation from semiconducting to metallic phase, accompanied by a structural transition in fluorinated WS2 (FWS2 ), is described. Fluorination enhances the stability of 1T FWS2 and makes it energetically favorable. The arena beyond conventional methods is opened for the synthesis of the 1T phase of transition metal dichalcogenides, proven to be superior in many applications.